Considerações sobre lúpus eritematoso sistêmico - Carneiro, Ana Cláudia Álvares [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Lupus is a rare autoimmune disease characterized by formation of the auto-antibodies which act against the body's own tissues. The patient produces harmful substances to your body and the antibody, which is a defense mechanism, becomes a mechanism of self-harm. It occurs more frequently in women, adults, latinos and black people. Lupus disease is divided into three types: Discoid Lupus Erythematosus, Systemic Lupus Erythematosus and Lupus Erythematosus Induced by Drugs. The involvement of the face occurs in 40 % to 50 % of patients diagnosed with systemic lupus erythematosus and is characterized by a rash shaped like a butterfly's wing that develops in the malar and nasal areas. The oral lesions associated with systemic lupus erythematosus are nonspecific, presenting erosive or atrophic or hyperkeratotic papules surrounded by streaks on lips, cheeks, palate and tongue. Have also been reported simultaneously oral candidiasis and xerostomia. The treatment of lupus erythematosus was nonspecific, since there is no standard protocol for all patients. Several measures are employed, between drugs and standards, in order to have a good quality of life. Patients with Systemic Lupus Erythematosus should avoid exposure to sunlight because ultraviolet radiation can trigger disease activity. They should always be done using sunscreens. The woman, who has lúpus, by performing a good treatment, is able to lead a normal life. Lupus is a serious disease, especially if there is kidney damage and brain injury, but it currently has a contingent with important therapeutic and most modern antibiotics that protect against infections and ensures longer survival of these patients. The aim of this study was to review current literature about the Lupus Erythematosus disease, focusing on the oral manifestations that occur most commonly in people affected by this disease, and the treatments currently performed

Lúpus é uma doença autoimune rara caracterizada pela formação de autoanticorpos que agem contra os próprios tecidos do organismo. O paciente fabrica substâncias nocivas para seu organismo e o anticorpo, que é um mecanismo de defesa, passa a ser um mecanismo de autoagressão. Ocorre mais frequentemente nas mulheres, adultos, latinos e negros. A doença lúpus é dividida em três tipos: Lúpus Eritematoso Discóide; Lúpus Eritematoso Sistêmico e Lúpus Eritematoso Induzido por Drogas. O acometimento da face ocorre em 40% a 50% dos pacientes diagnosticados com Lúpus Eritematoso Sistêmico e caracteriza-se por um exantema em forma de asa de borboleta que se desenvolve nas áreas malar e nasal. As lesões bucais associadas ao Lúpus Eritematoso Sistêmico são inespecíficas, apresentando-se erosivas ou atróficas, circundadas por pápulas hiperceratóticas ou estrias, em lábios, bochechas, palato e língua. Também têm sido relatadas simultaneamente monilíase bucal e xerostomia. O tratamento do Lúpus Eritematoso é inespecífico, pois não existe um protocolo padrão para todos os pacientes. Várias medidas são empregadas, entre medicamentos e normas, para que se tenha uma boa qualidade de vida. Os pacientes com Lúpus Eritematoso Sistêmico devem evitar exposição à luz solar, pois as radiações ultravioletas podem desencadear a atividade da doença. Deve ser sempre feito o uso de filtros solares. Através de um tratamento bem feito, a mulher portadora de lúpus tem condições de levar uma vida normal. O Lúpus é uma doença grave, especialmente se houver lesão renal e lesão cerebral, mas atualmente conta-se com um contingente terapêutico importante e com antibióticos mais modernos que protegem contra infecções e garantem sobrevida maior para essas pacientes. O objetivo...
Keywords: Lupus eritematoso sistêmico; Lúpus eritematoso discoide; Manifestações bucais; Lupus erythematosus, systemic